Socioeconomic Factors, Perioperative Complications, and 30-Day Readmission Rates Associated With Delayed Cranial Vault Reconstruction for Craniosynostosis. Issue 7 (October 2018) - Sergesketter, Amanda R.; Elsamadicy, Aladine A.; Lubkin, David T.; Kemeny, Hanna; Harward, Stephen C.; Krucoff, Kate B.; Krucoff, Max O.; Fuchs, Herbert; Thompson, Eric M.; Allori, Alexander C.; Marcus, Jeffrey R.; Muh, Carrie R.
Abstract : Background: Premature fusion of the cranial sutures can lead to significant neurocognitive, developmental, and esthetic consequences, especially if not corrected within the first year of life. This study aimed to identify the drivers of delayed cranial vault reconstruction (CVR) and its impact on complication and 30-day readmission rates among craniosynostosis patients. Methods: The medical records of all children who underwent CVR for craniosynostosis between 2005 and 2017 at an academic institution were retrospectively reviewed. A delay in operation was defined by surgery performed >12 months of age. Patient demographics, comorbidities, perioperative complication rates, and 30-day readmission rates were collected. Results: A total of 96 patients underwent primary CVR, with 79 (82.3%) patients undergoing nondelayed surgery and 17 (17.7%) patients undergoing surgery >12 months of age. Children undergoing delayed surgery were significantly more likely to be non-White ( P  < 0.0001), have Medicaid insurance ( P  = 0.023), and have a non-English primary language ( P  < 0.005). There was increased incidence of developmental disability identified at first consult (no-delay: 3.9% vs delay: 41.2%, P  < 0.0001) and increased intracranial pressure (no-delay: 6.3% vs delay: 29.4%, P  < 0.005) among children undergoing delayed surgery. The delayed cohort had a significantly higher unplanned 30-day readmission rate (no-delay: 0.0% vs delay: 5.9%, P  = 0.03). Conclusion: Our study suggests that craniosynostosis patients who are non-White, have a non-English primary language, and have Medicaid insurance are at risk for delayed primary surgery, which may lead to increased 30-day readmission. Interventions are necessary to reduce craniosynostosis patients' barriers to care to minimize the sequelae associated with delayed surgery.